Association of different Demographic characteristics with Hip Osteoarthritis patients attending the different Hospitals across the Karachi and Quetta - Aadil Ameer Ali; Natasha Bhutto; Shahmeer Chandio; Shoaib Waqas; Ali Raza Khoso; Muhammad Rafique; Muhammad Ismail; Shanza Iqbal (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2021)
Hip osteoarthritis (OA) is the most frequent and common among all degenerative joint disorders and affecting huge number of individuals. Older females and low income people are more likely to develop Hip OA. A cross sectional survey was conducted in different hospitals of Karachi & Quetta, Pakistan from July to September 2019. A self-constructed proforma was used among all 392 already diagnosed patients to collect the data and Spss version 23 was used to analyze the data. In demographic Characterstics the age, gender and household income were significantly associated with Hip OA (p<0.05). The study concluded that the people who were older, belongs to female gender and with low house hold income were found physically restrictive due to the hip OA. Older females and people with low income should be prioritized for the treatment of hip OA in order to reduce the restrictiveness from their activities of daily life and to enhance their physical functional capacity.